An evaluation of affordable housing needs in transit-oriented developments: The Citycenter Englewood TOD in Denver, Colorado - Benedick, Savanah (Kansas State University, 2010)
Affordable housing is an important component of Transit-Oriented Development (TOD) because it provides lower income households the option to live an automobile-free lifestyle. A TOD, for this research, can be defined as a development located next to a transit line which provides small-scaled amenities and pedestrian activities. It also integrates a mix of uses, such as residential, retail, and public uses. This report focuses on the residential portion of TOD by identifying the importance of affordable housing in Transit-Oriented Development. In order to explore affordable housing in TOD, a case study was conducted of an existing TOD in the Denver metropolitan region. This TOD, known as the CityCenter Englewood TOD, is specifically located in Englewood, Colorado. This report explores the policy decisions that Englewood made when deciding not to integrate affordable housing provisions into the development. The affordable housing situation in Englewood is rather complicated. A review of census data suggests that affordable housing is needed in the community, while community officials state that Englewood is contextually affordable compared to the Denver metropolitan region. The conclusion of this report identifies the characteristics of the Englewood community that portray little tangible need for additional affordable housing units in the year 2010. However, according to the “Best Practices” Study of this report, other TOD communities do show various levels of tangible need for a mixed-income environment.
Keywords: Transit; Housing; Affordable; Cost-burdened; Transportation (0709); Urban and Regional Planning (0999)